Food web transfer of biotoxins as part of a suite of multiple contaminants: a case study of brevetoxins and metals - Pouil, Simon; Clausing, Rachel; Metian, Marc; Bustamante, Paco; Bottein, Yasmine, Dechraoui (CCSD, 2018)
International audience Algal toxins in the environment are known to accumulate up the food chain via dietary pathways, often with little apparent effect on the health of the accumulating organism. Several laboratory studies on bivalves, however, have found that exposure to toxic dinoflagellates may alter important processes such as clearance rates or oxygen consumption. Neurotoxins produced by some of these algae have also been shown to act on ion channels in fish. These behavioral or physiological effects may, in turn, alter species responses to concurrent stressors in the environment, such as variable temperatures or salinity, or the presence of other contaminants (e.g. metals) often co-occurring with biotoxins in coastal waters. Experimental food chains involving toxic dinoflagellates provide amodel to assess interactions of toxin exposure with other environmental factors or contaminants in marine organisms. In this example, we examined the trophic transfer of brevetoxins (PbTxs) in a Karenia brevis-Mytilus edulis (blue mussel)-Scophthalmus maximus (turbot) food chain with simultaneous exposure to metals (combinations of radioisotopes 65Zn, 54Mn, 109Cd and 57Co). This modelallowed us to examine accumulation-depuration processes of PbTxs along the food web as well as how accumulated PbTxs affected metal uptake and assimilation. We found that after 4 days feeding with 980 ± 20 cellsKarenia brevis mL-1, mussels had accumulated 0.49 ± 0.22 μg PbTx eq g-1 wet wt in their soft tissues. Despite high toxin retention (78% remaining after 23 d depuration during metals exposure), PbTx exposure did not affect the assimilation of metals in mussels, excepting for small but significant increases inrates of 109Cd uptake. Turbot appeared to depurate dietary PbTxs more efficiently than mussels, as fish fed once with PbTx-containingmussel tissue contained similar concentrations of toxin in their viscera to those fed 15 times over 3 weeks. Similarly to mussels, assimilation of metals (65Zn and 54Mn) in turbot showed no ...